Activated L-Arginine/Nitric Oxide Pathway in Pediatric Cystic Fibrosis and Its Association with Pancreatic Insufficiency, Liver Involvement and Nourishment: An Overview and New Results - Folke Brinkmann (Journal of Clinical Medicine, 2020)
Cystic fibrosis (CF; OMIM 219700) is a rare genetic disorder caused by a chloride channel defect, resulting in lung disease, pancreas insufficiency and liver impairment. Altered L-arginine (Arg)/nitric oxide (NO) metabolism has been observed in CF patients’ lungs and in connection with malnutrition. The aim of the present study was to investigate markers of the Arg/NO pathway in the plasma and urine of CF patients and to identify possible risk factors, especially associated with malnutrition. We measured the major NO metabolites nitrite and nitrate, Arg, a semi-essential amino acid and NO precursor, the NO synthesis inhibitor asymmetric dimethylarginine (ADMA) and its major urinary metabolite dimethylamine (DMA) in plasma and urine samples of 70 pediatric CF patients and 78 age-matched healthy controls. Biomarkers were determined by gas chromatography–mass spectrometry and high-performance liquid chromatography. We observed higher plasma Arg (90.3 vs. 75.6 µM, p < 0.0001), ADMA (0.62 vs. 0.57 µM, p = 0.03), Arg/ADMA ratio (148 vs. 135, p = 0.01), nitrite (2.07 vs. 1.95 µM, p = 0.03) and nitrate (43.3 vs. 33.1 µM, p < 0.001) concentrations, as well as higher urinary DMA (57.9 vs. 40.7 µM/mM creatinine, p < 0.001) and nitrate (159 vs. 115 µM/mM creatinine, p = 0.001) excretion rates in the CF patients compared to healthy controls. CF patients with pancreatic sufficiency showed plasma concentrations of the biomarkers comparable to those of healthy controls. Malnourished CF patients had lower Arg/ADMA ratios (p = 0.02), indicating a higher NO synthesis capacity in sufficiently nourished CF patients. We conclude that NO production, protein-arginine dimethylation, and ADMA metabolism is increased in pediatric CF patients. Pancreas and liver function influence Arg/NO metabolism. Good nutritional status is associated with higher NO synthesis capacity and lower protein-arginine dimethylation.